Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have to prove that the ring $(B,+,*)$ is abelian only when for every $(a,b) \in B^2$, $(a+b)^2=a^2+2ab+b^2$.

I don't know where to start, and also I can relate $*$ to the ring, not $+$.

share|improve this question
    
You were missing a $2$ in the formula - it is certainly not the case in all abelian rings that $(a+b)^2=a^2+ab+b^2$. –  Thomas Andrews Dec 1 '12 at 17:45
2  
Although we talk about Abelian groups, for rings it's commutative rings. –  lhf Dec 1 '12 at 19:35

3 Answers 3

up vote 5 down vote accepted

Hint: Write out $$(a+b)^{2}=(a+b)(a+b)=a^{2}+ab+ba+b^{2}$$

note that in general you have to multiply this way since in some rings $ab\neq ba$ .

Now assume $$(a+b)^{2}=a^{2}+2ab+b^{2}$$ and compare both calculations. What do you get ?

share|improve this answer
1  
So,since we have * in the ring, I can write (a+b)*(a+b),which is = a^2+ab+ba+b^2 ,and compared to (a+b)^=a^2+2ab+b^2...i do the math and I have ab=ba so,yes this is an abelian ring,thanks! –  Alone1990 Dec 1 '12 at 17:59
    
@Alone1990 - I'm glad that helps! :) –  Belgi Dec 1 '12 at 18:24

Let $a,b\in B$. Then your hypothesis is that $(a+b)^2=a^2+2ab+b^2$. So $$ a^2+2ab+b^2=(a+b)^2=a^2+ab+ba+b^2. $$ Since we can cancel additive terms, we get $$ 2ab=ab+ba; $$ subtracting $ab$ from both sides, we get $ab=ba$.

share|improve this answer

Similarly, and more simply, the $ $ difference of squares $ $ formula is equivalent to commutativity

$$\rm\begin{eqnarray} a^2-b^2 &=&\,\rm (a-b)\,(a+b) \\ &=&\,\rm ab-ba\, +\, a^2-b^2 \\ \iff\ 0\, &=&\,\rm ab-ba \end{eqnarray}$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.